2021
DOI: 10.3389/fenvs.2021.725960
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Soil Microbial Community and Enzyme Activities to Shrub Species Artemisia gmelinii in Relation to Varying Rainfall in a Semiarid Land, SW China

Abstract: Widely distributed shrubs in drylands can locally alter soil physicochemical properties, which distinguish soil under plant canopy from soil outside the canopy. In the present study, we used a dominant shrub species Artemisia gmelinii in a semiarid land, SW China, to investigate the consequences of “shrub resource islands” for soil microbial communities and enzymatic activities. Such investigation was made at four sites that differed in rates of rainfall to examine how the consequences were altered by variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 74 publications
1
4
0
Order By: Relevance
“…AMF PLFAs increased with shrub patch size, which is consistent with the results of previous studies [ 20 , 29 ]. Significant positive correlations between the soil salt content and AMF PLFAs suggest that islands of salinity provide substrates that promote the growth of AMF by the colonization of spores [ 56 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…AMF PLFAs increased with shrub patch size, which is consistent with the results of previous studies [ 20 , 29 ]. Significant positive correlations between the soil salt content and AMF PLFAs suggest that islands of salinity provide substrates that promote the growth of AMF by the colonization of spores [ 56 ].…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies demonstrated that the fertile island of shrub enriched soil available nutrients under their canopy, such as SOM, N, and P, supplying more substrates for soil microbes [ 7 , 20 , 42 , 43 ]. Here, our results found shrub patch size had a positive effect on soil nutrient status.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations